Epidemiological analysis of the damage potential of Pgt-Ug99 in Central East, North East Africa; Iran and Punjab (India) - and J.C. ZADOKS, S. NAGARAJAN*, K.H. KOGEL (Indian Phytopathology, 2014)
In the Rift valley Epidemiological Zone that falls in the predicted Puccinia graminis tritici-Ug99 spread route from Uganda to India, is the presence of bi-modular annual rainy season, absence of a hot dry summer and the practice of two wheat growing seasons (the green bridge). This ensures the survival of Pgt in situ and the endogenous primary inoculum initiates the recurrence of the disease. While in the Indian Punjab Epidemiological Zone the exogenous primary inoculum of Pgt from the Himalaya to the plains of Indian Punjab gets subdued and at best builds-up traces of disease severity before the harvest of wheat. The Iranian Epidemiological Zone is similar to Indian Punjab, except that there is no monsoon and the exogenous inoculum of Pgt initiates stem rust development year and again. It is felt that Pgt-Ug99 lacks pre-eminence to threaten wheat production in the Indian Punjab.